Gender equality and equity in Costa Rican education challenges to evaluate - Vargas-Sandoval, Yensi (2021)
This essay raises the discussion on gender equality and equity in the highschool education system in Costa Rica. It offers a proposal of evaluative criteria to be applied to the actions of the Gender Equity and Equality Public Policy promulgated by the Ministry of Public Education. Through an approach to the social and educational context a general question is posed: In what way can the social evaluation of educational processes contribute to unveiling, in the spaces, the norms and the discourses located in the educational coexistence, the equality- inequality, as well as the naturalization and invisibility of unequal conditions from gender? From the evaluative discipline, the reflection exercise is underpinned by the pluralistic evaluation perspective, which is especially sensitive to inequalities, discrimination, stereotypes and violent expressions related to gender. This document offers an evaluative design that is based upon documentary research and performs a methodological disaggregation with questions, dimensions, variables and indicators of an evaluative nature. The conclusions indicate that the evaluation can and should contribute to promoting environments of healthy coexistence, free of discrimination and gender violence. In addition, it highlights that the general issue of equity and equality in the educational system is the responsibility of many actors and there are still challenges to face on a daily basis, since all of us must be involved in one way or another in the transformations that are required to eradicate gender violence